2015
DOI: 10.1073/pnas.1507386112
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule motions and interactions in live cells reveal target search dynamics in mismatch repair

Abstract: MutS is responsible for initiating the correction of DNA replication errors. To understand how MutS searches for and identifies rare base-pair mismatches, we characterized the dynamic movement of MutS and the replisome in real time using superresolution microscopy and single-molecule tracking in living cells. We report that MutS dynamics are heterogeneous in cells, with one MutS population exploring the nucleoid rapidly, while another MutS population moves to and transiently dwells at the replisome region, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 65 publications
6
95
0
Order By: Relevance
“…Notably, the change from fast to slow motion for PolC at the replisome is similar to the behavior we previously observed for the DNA mismatch repair protein MutS (35). It is possible that both proteins exhibit similar dynamics at the replisome simply because DNA binding on the chromosome occurs more readily at the replication fork where the DNA is unwound and more accessible.…”
Section: In Vivo Localization and Diffusion Of Polcsupporting
confidence: 81%
“…Notably, the change from fast to slow motion for PolC at the replisome is similar to the behavior we previously observed for the DNA mismatch repair protein MutS (35). It is possible that both proteins exhibit similar dynamics at the replisome simply because DNA binding on the chromosome occurs more readily at the replication fork where the DNA is unwound and more accessible.…”
Section: In Vivo Localization and Diffusion Of Polcsupporting
confidence: 81%
“…Our previous research investigating MutS1 has shown that B. subtilis MutS1-GFP forms foci that are recruited to the site of DNA synthesis (25)(26)(27)(28)48). Further, homologous recombination proteins and nucleotide excision repair proteins have been shown to form foci and localize to the nucleoid, respectively, following MMC treatment (44,49).…”
Section: Together These Results Indicate That the C-terminal Smr Dommentioning
confidence: 99%
“…As MMR is primarily a coreplicative process (Hombauer et al 2011;Liao et al 2015), most mutations in MMR-deficient cancers are replicative errors. Therefore, the strand biases observed in MSI cancers reveal the biases of corresponding polymerases without the confounding factor of MMR.…”
Section: Discussionmentioning
confidence: 99%
“…As MMR is primarily a coreplicative process (Hombauer et al 2011;Liao et al 2015), we hypothesized that this asymmetry is due to a joint effect of the differences in rates of mismatches produced by replicative polymerases on the leading and on the lagging strands, and differences in number of mutations repaired by the MMR between the two strands. To investigate this question, we employed data from patients with inherited biallelic MMR deficiency (bMMRD) and somatic mutations in one of the two major replicative polymerases, Pol epsilon (mutated Pol epsilon) or Pol delta (mutated Pol delta).…”
mentioning
confidence: 99%